Pengaruh Model Pembelajaran Project Based Learning Berbantuan Modul Terhadap Peningkatan Keterampilan Proses Sains Pada Materi Kemagnetan - Widia Br Ginting; Nuraini Fatmi; Halimatus Sakdiah; Fajrul Wahdi Ginting; Desy Sary Ayunda (Departement of Mathematics Education, 2024)
Project-based learning is a learning model that involves students directly into learning activities that are useful for solving problems in their lives and are skilled. The purpose of this study is to determine the effect of the module-assisted Project Based Learning learning model on improving science process skills on magnetic materials. The modules used aim to make learners an independent individual and can work together with a team.The research method used is the experimental method, the research design used is quasi-experimental design. The research was applied in MTsN 2 North Aceh, class IX in the even semester of the 2023/2024 academic year, in class IX-G as an experimental class of 22 people and class IX-A as a control class of 22 people. Data collection techniques taken through pretest and posttest as well as observation sheets. 10 multiple-choice questions as pretest posttest and a reliable 0.995 score with a very high category. The average score of the experimental class pretest with a value of 4.18 and the posttest with a value of 8.36 and the average score of the control class pretest with a value of 5.77 and the posttest with a value of 8.77. Then the hypothesis test showed a significant value of 2 tailed 0.202 < 0.05. The observation results showed that the skill aspect of the science process, namely observing (observation) reached 100% and obtained N-gain of 0.69 in the medium category.The results of the study showed an increase in students' posttest pretest scores and aspects of good science process skills. In conclusion, there is an influence of the module-assisted project based learning model on improving science process skills on magnetic material in MTs N 2 North Aceh. The researcher's suggestion is that you should use practical tools and materials for projects, modules that have been designed and pay attention to time in the learning process and making projects.